Dietary supplement usage, motivation, and education in young Canadian athletes - Wiens, K.; Erdman, K. A.; Stadnyk, M.; Parnell, J. A. (International Journal of Sport Nutrition and Exercise Metabolism, 2014)
To evaluate dietary supplement use in young Canadian athletes, their motivation for consuming supplements, and their sources of information. Methods: A questionnaire tested for content validity and reliability was administered to 567 athletes between the ages of 11 and 25 years from the Canadian athletic community in face-to-face meetings. Demographics and sport variables were analyzed using descriptive statistics. Fisher`s exact tests were used to examine dietary supplementation patterns and sources of information regarding dietary supplement use between categories of gender, age, sport type, and competition level. Results: Ninety-eight percent of athletes were taking at least one dietary supplement. Males were more likely to consume protein powder, energy drinks, recovery drinks, branched chain amino acids, beta-alanine, and glutamine (p < .01); supplements typically associated with increased muscle mass. Athletes 11-17 years old focused on vitamin and mineral supplements; whereas, athletes 18-25 years old focused on purported ergogenic supplements. Strength training athletes were more likely to consume creatine, glutamine, and protein powders (p < .02). Reasons for supplement use included to stay healthy, increase energy, immune system, recovery, and overall performance. Primary sources of information were family and friends, coaches, and athletic trainers; with 48% of athletes having met with a dietitian. Preferred means of education included individual consultations, presentations, and the internet. Conclusions: The majority of young athletes are using dietary supplements with the belief they will improve performance and health; however, may not always have reliable information. Educational programs using individual consultations and electronic media are recommended for this demographic